2015
DOI: 10.18311/mvpjms/2015/v2/i2/784
|View full text |Cite
|
Sign up to set email alerts
|

Study of Homologous Autoimplantation Therapy for Treatment of Multiple Warts in Patients Attending the Dermatology out Patient Department

Abstract: Introduction: Warts are benign tumours that commonly involve skin and other epithelial tissues. There is no single treatment modality that is 100% effective. In multiple warts, especially on face, palms, and soles destructive procedure are inappropriate and impractical. Homologous autoimplantation is a simple technique, which helps in inducing cell mediated response, causing clearance of warts. Aims and objectives: To evaluate the effect of homologous autoimplantation therapy in treatment of multiple warts. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 8 publications
2
9
2
Order By: Relevance
“…Gugle et al reported least response in plane warts (34.49% reduction in mean number of warts). 8 In contrast to our findings, Ghosh and Maplestone reported cure in 9 of 12 patients with plane warts and significant improvement in those who were not cured. 11 Gugle et al reported maximum response in filiform warts (93.28% reduction in mean number) which contrasts the findings of our study (13.11% reduction in the mean number).…”
Section: Subgroup Analysiscontrasting
confidence: 99%
See 4 more Smart Citations
“…Gugle et al reported least response in plane warts (34.49% reduction in mean number of warts). 8 In contrast to our findings, Ghosh and Maplestone reported cure in 9 of 12 patients with plane warts and significant improvement in those who were not cured. 11 Gugle et al reported maximum response in filiform warts (93.28% reduction in mean number) which contrasts the findings of our study (13.11% reduction in the mean number).…”
Section: Subgroup Analysiscontrasting
confidence: 99%
“…Infection at the autoinoculation site has been reported in 2.4-6.12% cases in other studies. 4,7,8 One patient complained of persistent pain at the autoinoculation site which subsided after 2-3 weeks. Two patients had persistent erythema without pain at the autoinoculation site which resolved after 5-6 weeks.…”
Section: Subgroup Analysismentioning
confidence: 99%
See 3 more Smart Citations